Harvesting solar power in India! - Ashok Gulati; Stuti Manchanda; Rakesh Kacker (Indian Council for Research on International Economic Relations (ICRIER), 2016)
Prime Minister Narendra Modi has set an ambitious target of 100,000 MW of solar power capacity to be achieved by 2022, when India celebrates 75 years of her independence. This is a grand vision for ushering in a sort of revolution in clean energy in India in the next six years. In a country that generates more than 60 percent of its power by burning coal, and where air quality is fast worsening in several Indian cities, the need for clean energy cannot be overstated. Interestingly, Prime Minister Modi has also set another ambitious target of doubling farmers' incomes by 2022! The uppermost question in everyone's mind is: can these targets be achieved by 2022? This is particularly so when the current solar power capacity in the country has just touched 8000 MW by July end, 2016, and no country in the world has such an ambitious target as India has set out for 2022. On farmers' real incomes, the compound annual growth rate (CAGR) in the recent past (FY2003 to FY 2013) has been mere 3.5 percent; and doubling these incomes by 2022 would mean increasing this CAGR from 3.5 percent to more than 12 percent. Despite these stunningly ambitious targets, our take in this paper is that a significant progress can be made towards achievement of both of these goals, provided both are conceived and implemented in unison, a sort of marrying each other, with innovative policies- like the guaranteed feed-in-tariffs (FIT) for solar power generated on farmers' fields- to back this alliance. It should not be a difficult proposition as FIT already exists in case of wind energy, the scale of which is much more (27 GW) than that of solar power (8GW). Since the costs of solar power have come down drastically during the last couple of years, and now compete very well with the costs of power generation from burning coal, this would help generate clean energy in a cost effective manner as well as help augment farmers' real incomes. A true model of competitiveness with inclusiveness, and this can be scaled up in a sustainable manner. This will also help to reduce power subsidies of state electricity boards (SEBs), wherever solar power can substitute existing connections. Our confidence in approaching these twin goals comes from the rapidly falling costs of solar power (by about 70percent since 2010-11) and its champion support, which comes from the highest political level, i.e., the Prime Minister himself, and no opposition from any other political parties for such a bold initiative. The only thing to be seen is how to raise advance capital funds to get this going, how to organize farmers on these lines, how to convince the discoms for guaranteed feed-in-tariffs, and how long it is persevered till the goals are reached! In undertaking such gigantic twin missions, it is always wise to look for best practices and technologies around the world. Japan, China, UK, Israel all offer interesting examples, but the global leader in solar power today is Germany. And it has a lot to offer India, with a win-win collaboration between business to business (B2B) on both sides as well as government to government (G2G) Memorandum of Understanding (MOU) to facilitate transfer of technologies, skills, training and practices, and above all some long term finances. Such an Indo-German alliance for solar power can be a catalyst of change not only generating clean energy but also building green Indian agri-value chains and directly augmenting farmers' incomes. This will be a global showcase of competiveness with inclusiveness and the time to take up this idea and scale it up is NOW!
Keywords: L94; Q180; Q150; 330; Solar Power; Agriculture; Feed-in-Tariffs; India; Farmer Income